Coronary heart disease risk factors: effectiveness of their control by primary health doctors (survey data) - D. M. Aronov; N. M. Akhmedzhanov; L. A. Gutkovskaya; O. Yu. Sokolova; A. Sh. Tkhostov; E. I. Pervichko; R. G. Oganov (Российский кардиологический журнал, 2006)
The survey focused on municipal out-patient clinic internists' involvement into modified coronary heart disease risk factor (CHD RF) control, as well as on RF control effectiveness reported by the patients. Up to 73 % of the doctors confirmed clinical effectiveness of the intervention, and 53 % regarded it equally important as antianginal therapy. Nevertheless, there were numerous barriers for successful realization of CHD RF control measures. Delivering RF control advice was linked to doctors' working pressure in 50, 5 % of cases, to patients' cultural level in 78,8 %, to patients' interest and initiative in 33,3 %, and to personal patient-doctor relations in 21,2 %. Only brief advice was given by 44,9 % of the doctors, and no more than 18 % of the respondents were ready to forward their patient to the relevant specialist. Therefore, 26 % of the doctors reported providing lifestyle modification advice «never», «rarely», or «occasionally». Unsatisfactory follow-up on fulfillment of such advice was confirmed by 49 % of the doctors. According to patient-provided data, the majority of the patients were unable to recollect receiving any relevant advice from their doctors. Most doctors reported advising on lipid-lowering diet, body weight control and smoking cessation (94 % in each case), or physical training (77,5 %), but only 46,1 %, 32,3 %, 75,3 % and 23,8 % of their patients, respectively, confirmed receiving such recommendations. Moreover, even for smoking cessation advice, where doctor-patient reporting gap was minimal, only 13, 4 % of the patients confirmed being offered some cessation plan. Expectedly, the majority of quitters (68,85 %) were sure that cessation was their own accomplishment.